1990
DOI: 10.1068/p190675
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception and the Guidance of Locomotion without Vision to Previously Seen Targets

Abstract: Two experiments were performed to assess the accuracy and precision with which adults perceive absolute egocentric distances to visible targets and coordinate their actions with them when walking without vision. In experiment 1 subjects stood in a large open field and attempted to judge the midpoint of self-to-target distances of between 4 and 24 m. In experiment 2 both highly practiced and unpracticed subjects stood in the same open field, viewed the same targets, and attempted to walk to them without vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
255
2
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(285 citation statements)
references
References 18 publications
19
255
2
5
Order By: Relevance
“…That is, having visually previewed a target as much as 20 m away (Rieser, Ashmead, Talor, & Youngquist, 1990), a person can close his or her eyes and walk to it fairly accurately and without bias. Indeed, walking without visual feedback is one of a number of indirect measures of distance perception (including throwing without feedback) at which humans perform especially well (e.g., Thomson, 1983; see Loomis & Beall, 2004, for a review).…”
mentioning
confidence: 99%
“…That is, having visually previewed a target as much as 20 m away (Rieser, Ashmead, Talor, & Youngquist, 1990), a person can close his or her eyes and walk to it fairly accurately and without bias. Indeed, walking without visual feedback is one of a number of indirect measures of distance perception (including throwing without feedback) at which humans perform especially well (e.g., Thomson, 1983; see Loomis & Beall, 2004, for a review).…”
mentioning
confidence: 99%
“…Both the GVR and NGVR The GVR and virtual rotating rooms were cylindrically shaped with a simulated diameter of 20 m and height of 4 m and a rotating speed of 30 degrees per second to match with the treadmill walking speed. Previous studies have shown rotation rates close to this to be effective in causing sensations of self-motion [30,36]. The subject's simulated eyepoint was displaced 1.8 m above, 7 m left and 1 m back from the center of the both of the room's floor as it rotated about an axis coincident with its center, creating the illusion that the subject was walking around the perimeter of the room to his or her left.…”
Section: Virtual Reality Scene Generationmentioning
confidence: 99%
“…Our previous study had shown a significant difference in the strategic torso stabilization responses during locomotion control when viewing polarized scenes in comparison to viewing non-polarized scenes that were rotated about or translated along all the degrees of freedom [36]. Other studies have shown the importance of optic flow and that optic flow in a virtual scene, clearly influences locomotion trajectory [44].…”
Section: The Effects Of Visual Scene Polarity In Controlling Locomotomentioning
confidence: 99%
“…While many studies have shown, similar to Thomson, that blindfolded humans are able to navigate relatively successfully towards a target, his suggestion of a time limiting component has not been replicated (Fukusima, Loomis, & Da Silva, 1997;Rieser, Ashmead, Talor, & Youngquist, 1990), with many authors finding that participants become less accurate in their estimation if the distance is increased (Corlett, Patla, & Williams, 1985;Fukusima et al, 1997;Glasauer, Amorim, Vitte, & Berthoz, 1994;Loomis, Da Silva, Fujita, & Fukusima, 1992;Mittelstaedt & Mittelstaedt, 2001;Rieser et al, 1990;Steenhuis & Goodale, 1988). Indeed, there is good evidence to suggest that other factors apart from time can contribute to successful non-visual distance estimation.…”
Section: Introductionmentioning
confidence: 99%